Exposing latent fingermarks on problematic metal surfaces using time of flight secondary ion mass spectroscopy - Thandauthapani, Tshaiya Devi; Reeve, Adam J.; Long, Adam S.; Turner, Ian J.; Sharp, James S. (Elsevier, 2018)
Fingermarks are a key form of physical evidence for identifying persons of interest and linking them to the scene of a crime. Visualising latent (hidden) fingermarks can be difficult and the correct choice of techniques is essential to develop and preserve any fingermarks or other (e.g. DNA) evidence that might be present. Metal surfaces (stainless steel in particular) have proven to be challenging substrates from which to reliably obtain fingermarks. This is a great cause for concern among police forces around the globe as many of the firearms, knives and other metal weapons used in violent crime are potentially valuable sources of fingermark evidence. In this study, a highly sensitive and non-destructive surface science technique called time of flight secondary ion mass spectroscopy (ToF-SIMS) was used to image fingermarks on metal surfaces. This technique was compared to a conventional superglue based fuming technique that was accompanied by a series of contrast enhancing dyes (basic yellow 40 (BY40), crystal violet (CV) and sudan black (SB)) on three different metal surfaces. The conventional techniques showed little to no evidence of fingermarks being present on the metal surfaces after a few days. However, ToF-SIMS revealed fingermarks on the same and similar substrates with an exceptional level of detail. The ToF-SIMS images demonstrated clear ridge definition as well as detail about sweat pore position and shape. All structures were found to persist for over 26 days after deposition when the samples were stored under ambient conditions.